MayNet: A Neural Network Ensemble Approach Based on May's Theorem for Improved Classification - Zhang, Jincheng; Zhang, Jindong (Peneliti Teknologi Teknik Indonesia, 2024)
In this study, we explored the possibility of applying May's Theorem to neural networks and proposed a new unified network architecture called MayNet. MayNet achieves category prediction by integrating multiple neural network